New records and ecological observations on Greek cave crickets (Orthoptera: Rhaphidophoridae) - Davranoglou, L-R; Matsumoto, K; Soh, Z; Kempton, J (Taylor and Francis, 2021)
We record Dolichopoda lustriae Rampini & Di Russo, 2008 (Orthoptera: Ensifera: Rhaphidophoridae) from the Pindus mountain range in Epirus, Greece, more than 200 km to the north of the type locality in Aetolia-Acarnania. We show that this species has an unusually broad distribution for a Balkan cave cricket, and can also live independently of caves, instead inhabiting the crevices of large rock formations. We found D. lustriae to be sympatric with Troglophilus zorae Karaman & Pavićević, 2011, whose presence in Greece is recorded for the first time in this study. We provide high-quality photographs of the habitus and genitalia of D. lustriae and re-describe its morphology. Detailed information about the habitat, behaviour of the D. lustriae is also provided, and possible measures for its conservation are suggested.